How Do Video Games Elicit Guilt in Players? Linking Character Morality to Guilt Through a Mediation Analysis - Ahn, Changhyun; Grizzard, Matthew; Lee, Seyoung (Frontiers in Psychology, 2021)
Research has consistently found that committing immoral actions in video games is capable of eliciting feelings of guilt in players. This study aimed to investigate the mediating role of theoretically-relevant psychological mechanisms: Perceived morality of the player-controlled character and self-attribution of virtual behavior. Based in psychological and communication theory, we derived a model that links these variables to character portrayal and guilt. A between-subjects experiment manipulated the portrayal of the player-controlled character (immoral vs. moral) and measured the mediating variables and self-reported guilt. The hypothesized model was tested using a path model. Data were generally consistent with hypotheses. Controlling an immoral character reduced perceived character morality. Perceived character morality positively predicted self-attribution of character behavior and negatively predicted guilt. Self-attribution positively predicted guilt but self-attribution and perceived character morality did not interact. Our findings suggest novel directions for continued research into how game features elicit emotional responses in players.